Numerical Analysis of a Soil-Steel Bridge Structure - Damian Beben (The Baltic Journal of Road and Bridge Engineering)
The paper presents a numerical analysis of the soil-steel bridge which was also thoroughly tested under real field loads (during backfilling and under static loads). The comparison of results from calculations and field tests was also presented in the paper. The soil-steel structures are built mostly as bridges located on local roads, but also as the railway viaducts, or even as the highway bridges as well as recently as the ecological objects or tunnels (overpasses and underpasses for animals). The technology of usage of flexible structures made from corrugated steel plates (CSP) is based on the interaction between shell and surrounding soil (backfill) and also takes into consideration the effect of loads arching in soil. The computation model with interface elements can be used to computer simulation of live loads in such type of bridges instead of extremely expensive and time-consuming experimental tests.